2008
DOI: 10.1074/jbc.m709835200
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage-induced Ubiquitylation of RFC2 Subunit of Replication Factor C Complex

Abstract: Many proteins involved in DNA replication and repair undergo post-translational modifications such as phosphorylation and ubiquitylation. Proliferating cell nuclear antigen (PCNA; a homotrimeric protein that encircles double-stranded DNA to function as a sliding clamp for DNA polymerases) is monoubiquitylated by the RAD6-RAD18 complex and further polyubiquitylated by the RAD5-MMS2-UBC13 complex in response to various DNA-damaging agents. PCNA mono-and polyubiquitylation activate an error-prone translesion synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…28,29 It has been shown that, in the absence of pRb, negative cell growth genes, including other Rb family members, may be upregulated to compensate for pRb function. [30][31][32] Correlating with this, microarray analysis showed upregulation of Rbl1 (p107), Cdkn1a (p21 Cip1 ) and Cdkn2d (p19 Ink4d ) in the pRb -/-inner ear.…”
Section: Resultsmentioning
confidence: 99%
“…28,29 It has been shown that, in the absence of pRb, negative cell growth genes, including other Rb family members, may be upregulated to compensate for pRb function. [30][31][32] Correlating with this, microarray analysis showed upregulation of Rbl1 (p107), Cdkn1a (p21 Cip1 ) and Cdkn2d (p19 Ink4d ) in the pRb -/-inner ear.…”
Section: Resultsmentioning
confidence: 99%
“…C mutations were not impaired in the absence of PCNAK164 modification. These observations suggest that not all specialized DNA polymerases depend on PCNA monoubiquitination specifically, but on other ubiquitinated factors [177,178] such as the heterotrimeric Rad9/Rad1/Hus1 sliding clamp (9-1-1 complex) and replication factor C (which can also be ubiquitinated by the Rad6/Rad18 complex) [179,180] or unidentified ubiquitinated components in the replication machinery. Recent data showing that ubiquitinated PCNA is not the only ubiquitinated target that drives Polg into foci, support this idea [45].…”
Section: Mechanisms Of Pcna Monoubiquitination and Dna Polymerase Swimentioning
confidence: 95%
“…In addition to RPA32, it is possible that other cellular replication proteins are modified during the AAV-induced DDR. Cellular minichromosome maintenance proteins are phosphorylated during DNA damage (17,37,68) while RFC2/RFC4 and PCNA can become ubiquitinated (44,78). It will be interesting to determine how AAV-induced signaling impacts these replication factors and their function during productive AAV replication.…”
Section: Discussionmentioning
confidence: 99%